Cryphalus lipingensis Tsai & Li, 1963 - Yiyi Dong; Andrea Lucky; Jiri Hulcr (EDIS)
Cryphalus lipingensis Tsai & Li, 1963 belongs to the bark beetle genus Cryphalus that contains more than 200 species. Five species of Cryphalus are distributed throughout the USA, mostly in northern latitudes. All American species live in dead twigs of conifers, and none of these species is considered an important pest. Cryphalus lipingensis does not occur in North America, but it is widespread in China. The reason for its importance is that it has been reported to colonize and kill American pine species planted in China, namely slash pine, Pinus elliottii, and as such poses a threat to US forests and forestry as a potential invasive pest.